Specific MRI Abnormalities Reveal Severe Perrault Syndrome due to CLPP Defects - Theunissen, Tom E. J.; Szklarczyk, Radek; Gerards, Mike; Hellebrekers, Debby M. E. I.; Mulder-Den Hartog, Elvira N. M.; Vanoevelen, Jo; Kamps, Rick; de Koning, Bart; Rutledge, S. Lane; Schmitt-Mechelke, Thomas; van Berkel, Carola G. M.; van der Knaap, Marjo S.; et al. (Frontiers in Neurology, 2016)
In establishing a genetic diagnosis in heterogeneous neurological disease, clinical characterization and whole exome sequencing (WES) go hand-in-hand. Clinical data are essential, not only to guide WES variant selection and define the clinical severity of a genetic defect, but also to identify other patients with defects in the same gene. In an infant patient with sensorineural hearing loss, psychomotor retardation and epilepsy, WES resulted in identification of a novel homozygous CLPP frameshift mutation (c.21delA). Based on the gene defect and clinical symptoms, the diagnosis Perrault syndrome type 3 (PRLTS3) was established. The patient’s brain-MRI revealed specific abnormalities of the subcortical and deep cerebral white matter and the middle blade of the corpus callosum, which was used to identify similar patients in the Amsterdam brain-MRI database, containing over 3000 unclassified leukoencephalopathy cases. In three unrelated patients with similar MRI abnormalities the CLPP gene was sequenced, and in two of them novel missense mutations were identified together with a large deletion that covered part of the CLPP gene on the other allele. The severe neurological and MRI-abnormalities in these young patients were due to the drastic impact of the CLPP mutations, correlating with the variation in clinical manifestations among previously reported patients. Our data shows that similarity in brain-MRI patterns can be used to identify novel PRLTS3 patients, especially during early disease stages, when only part of the disease manifestations are present. This seems especially applicable to the severely affected cases in which CLPP function is drastically affected and MRI abnormalities are pronounced.